Design System of Controlling Admission of New Students STIKOM Surabaya Study case : Campus Expo 2012 - Metawati, Gema Pertiwi Aisyah; Wibowo, Januar; Agastya, Waldy Permana (Jurnal JSIKA, 2012)
An admission is a part of structural management at STIKOM Surabaya that has main function as marketing and sales. At the time of carrying out activities, Penmaru’s often have difficulties. Difficulty that frequently happened is lack of coordination between coordinator and Person In Charge (PIC) on activities preparation. Besides that, another difficulty is there is no up to date data that can describes completion of each activities, so that on activities implementation frequently not performing well. Workflow is a Information Technology (IT) that using electronic system to organizing and monitoring business process. Web-Based Application with workflow application used as monitoring and controlling Penmaru’s activities. Based on blackbox testing and evaluation result against application user respondents, found that this activities controlling system can monitoring and controlling perform of each activities. Even application or system have been made to and capable to monitoring and controlling with activities warning by e-mail and SMS. So every activity both in terms of planning, controling and implementation can be coordinated well. Keywords : Activity ,workflow, warning